(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The position of schedule caste and schedule tribe is always a question mark foe the society. being a developing country we are saying that we are giving equal statue to them as compared with other caste but in reality its not be like this . In modern time also they are facing problem but we can say that the extent of sufferingness is less as compared to previous time. For improving their conditions government are taking various steps like specific laws are being made for them , commissions were made only for their betterment and by means of reservation also ,government is trying to improve their condition . Specifically Our Constitution guarantees justice and equality of opportunity to all its citizens. It also recognizes that equal opportunity implies competition between equals, and not ‘un-equals’. Recognizing the inequality in our social structure, the makers of the Constitution argued that weaker sections have to be dealt with on a preferential footing by the state. A special responsibility was, thus, placed upon the state to provide protection to the weaker sections of society.Accordingly, the Constitution provided for protective discrimination under various articles to accelerate the process of building an egalitarian social order. Thus, preferential treatment for the depressed classes (SCs and STs), should not be understood as an act of magnanimity on the part of the political elite at the national level but rather a strategy to give them a share in power in politics and administration and to uplift them socially and economically.